A Feasibility Study on 3D Bioprinting of Microfat Constructs Towards Wound Healing Applications - Schmitt, Trevor; Katz, Nathan; Kishore, Vipuil (Frontiers in Bioengineering and Biotechnology, 2021)
Chronic wounds affect over 400,000 people in the United States alone, with up to 60,000 deaths each year from non-healing ulcerations. Tissue grafting (e.g., autografts, allografts, and xenografts) and synthetic skin substitutes are common treatment methods, but most solutions are limited to symptomatic treatment and do not address the underlying causes of the chronic wound. Use of fat grafts for wound healing applications has demonstrated promise but these grafts suffer from low cell viability and poor retention at the wound site resulting in suboptimal healing of chronic wounds. Herein, we report on an innovative closed-loop fat processing system (MiniTCTM) that can efficiently process lipoaspirates into microfat clusters comprising of highly viable regenerative cell population (i.e., adipose stromal cells, endothelial progenitors) preserved in their native niche. Cryopreservation of MiniTCTM isolated microfat retained cell count and viability. To improve microfat retention and engraftment at the wound site, microfat was mixed with methacrylated collagen (CMA) bioink and 3D printed to generate microfat-laden collagen constructs. Modulating the concentration of microfat in CMA constructs had no effect on print fidelity or stability of the printed constructs. Results from the Alamar blue assay showed that the cells remain viable and metabolically active in microfat-laden collagen constructs for up to 10 days in vitro. Further, quantitative assessment of cell culture medium over time using ELISA revealed a temporal expression of proinflammatory and anti-inflammatory cytokines indicative of wound healing microenvironment progression. Together, these results demonstrate that 3D bioprinting of microfat-laden collagen constructs is a promising approach to generate viable microfat grafts for potential use in treatment of non-healing chronic wounds.